Progesterone receptor expression in granulosa cells is suppressed by microRNA-378-3p. (5th January 2015) - Toms, Derek; Xu, Shengyu; Pan, Bo; Wu, De; Li, Julang
Highlights: miR-378-3p is expressed in ovarian granulosa cells, and decreases during maturation. A conserved binding site in progesterone receptor was confirmed by luciferase reporter assays. Targeting of progesterone receptor by miR-378-3p decreased downstream gene expression. miR-378-3p may play a role in mediated follicular development by regulating key pathways. Abstract: In developing ovarian follicles, the progesterone receptor (PGR) is essential for mediating transcription of key factors that coordinate cellular functions including follicular remodeling. With recent investigations examining the role of microRNA (miRNA) in regulating ovarian function we used a lentiviral approach to over express miR-378 in cultured primary porcine granulosa cells to study the role this miRNA may play in granulosa cell development. We revealed that miR-378-3p decreased protein levels and mRNA levels of PGR via targeting its 3′UTR. We observed that this regulation of PGR by miR-378-3p resulted in a corresponding decrease in gene transcripts of ADAMTS1, CTSL1, and PPARG, all known to be regulated by PGR and important for follicular maturation and remodeling. Our study provides the first evidence for post-transcriptional regulation of PGR and further elucidates the role of miR-378-3p in the ovary.